ChemInform Abstract: Highly Diastereoselective 1, 6‐Conjugate Addition of Arylboronic Acids to Securinine. Issue 35 (August 2016) - Perez, Marc; Ayad, Tahar; Maillos, Philippe; Poughon, Valerie; Fahy, Jacques; Ratovelomanana‐Vidal, Virginie
Abstract: Rhodium catalysis provides access to the single diastereomers of the regioselective C15‐arylation products of securinine in good yields.